A Comparison of the Simulations and Observations for a Nearby Spiral Arm - Piecka, Martin; Paunzen, Ernst (Frontiers in Astronomy and Space Sciences, 2021)
We present a review of our current understanding of the spiral structure of galaxies, based on the kinematic models. The analysis is focused on the ability of galactic open clusters to trace the spiral arms, based on the recent data releases from Gaia. For this, a simple 1D description of the motion of spiral arms and clusters is introduced. As next step, results are verified using a widely-accepted kinematic model of the motion in spiral galaxies. As expected, both approaches show that open clusters older than about 100 Myr are bad tracers of spiral arms. The younger clusters (ideally <30 Myr) should be used instead. This agrees with the most recent observational evidence. The latest maps of the diffuse interstellar bands are compared with the spiral structure of the Milky Way and the Antennae Galaxies. The idea of these bands being useful for studying a galactic structure cannot be supported based on the current data.